The future of intelligence : challenges in the 21st century - Duyvesteyn, Isabelle , 1972-; Jong, Ben de , 1947-; Reijn, Joop van (Studies in intelligence series, 2014)
"This volume discusses the challenges the future holds for different aspects of the intelligence process and for organisations working in the field. Gone are the days when the main focus of Western intelligence services was on the intentions and capabilities of the Soviet Union and its allies. Instead, at present, there is a plethora of threats and problems that deserve attention. Some of these problems are short-term and potentially acute, such as terrorism. Others, such as the exhaustion of natural resources, are longer-term and by nature often more difficult to foresee in their implications. This book analyses the different activities that make up the intelligence process, or the 'intelligence cycle', with a focus on changes brought about by external developments in the international arena, such as technology and security threats. Drawing together a range of key thinkers in the field, The Future of Intelligence examines possible scenarios for future developments, including estimations about their plausibility, and the possible consequences for the functioning of intelligence and security services. This book will be of much interest to students of intelligence studies, strategic studies, foreign policy, security studies and IR in general"